PENGENALAN HTML DAN CSS BAGI SISWA SMK SEBAGAI PERSIAPAN MENUJU ERA DIGITAL - Ahmad Fauzi; Asih Hasanah; Dea Septina; Khoirootun Hisan; Mugi Yanto; Muhammad Luthfi Ghifar; Oktaviyanus; Siti Adawiyah; Siti Aisyah Oktaviani; Siti Marlina; Eka Sri Rahayu (Abdi Jurnal Publikasi, 2025)
The digital era demands mastery of technological skills as basic competencies for young generations. This paper outlines a community service program aimed at introducing HTML and CSS as the foundation of web development to students at SMK Daarul Shafa. The program is designed to bridge the digital divide by focusing on mastering markup language and styling which form the basis of web application development. The main objectives of the program include providing comprehensive understanding of the basic structure of HTML, application of CSS for visual design, development of simple web-based projects, and building computational thinking mindset. Program implementation involves project-based learning methods that integrate direct practice, problem solving, and collaboration. Despite facing challenges in the form of limited infrastructure and varying levels of digital literacy among students, the program successfully improved technical skills and soft skills such as creativity, problem solving, and teamwork. Program results show significant improvement in understanding basic web development concepts and students' confidence in using technology. This program serves as a strategic step in preparing students to face digital transformation, while supporting Indonesia's vision to enhance human resource competitiveness in the digital era